IoT-Based Kitchen Monitoring System with ESP32 and Firebase Realtime - FAJAR RAHAYU; ANDHIKA OCTA; HERI HARDIYANTO (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2026)
LPG gas leaks and unmonitored kitchen environmental conditions can trigger fires and endanger health. This study developed an Internet of Things (IoT)-based kitchen monitoring system to detect Liquefied Petroleum Gas (LPG) leaks and environmental conditions in real-time. The system uses an MQ-2 sensor as an LPG gas detector, a DHT11 sensor for temperature and humidity, an MQ-135 for air quality, and an LDR for light intensity integrated with an ESP32 microcontroller and the Firebase Realtime Database. Sensor data is sent in real-time via a Wi-Fi network and displayed on an Android application with warning notifications. Performance evaluation was carried out by measuring the delay in data transmission from the sensor to the application in household kitchen conditions. Test results showed an average delay in the range of 0.24–0.36 seconds, which still meets the needs of an early warning system. This system is considered effective in improving the safety of LPG-based kitchens through real-time monitoring and fast notifications.